2020
DOI: 10.3390/ijms21228858
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection via Metabolism for Rat Heart Preservation Using the High-Pressure Gaseous Mixture of Carbon Monoxide and Oxygen

Abstract: The high-pressure gas (HPG) method with carbon monoxide (CO) and oxygen (O2) mixture maintains the preserved rat heart function. The metabolites of rat hearts preserved using the HPG method (HPG group) and cold storage (CS) method (CS group) by immersion in a stock solution for 24 h were assessed to confirm CO and O2 effects. Lactic acid was significantly lower and citric acid was significantly higher in the HPG group than in the CS group. Moreover, adenosine triphosphate (ATP) levels as well as some pentose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Speculatively, Oroxylin A suppresses the R5P concentration by possibly inhibiting the pentose phosphate pathway and, consequently, purine metabolism, by decreasing the supply of PRPP, which is required for ATP generation and purine nucleotide biosynthesis in F. graminearum ( Figure 5 B) [ 28 , 29 ]. Alternatively, a downregulated pentose phosphate pathway may result in decreased NADPH generation and increased oxidative stress, which imbalances the redox system in F. graminearum , thereby retarding its growth and development [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Speculatively, Oroxylin A suppresses the R5P concentration by possibly inhibiting the pentose phosphate pathway and, consequently, purine metabolism, by decreasing the supply of PRPP, which is required for ATP generation and purine nucleotide biosynthesis in F. graminearum ( Figure 5 B) [ 28 , 29 ]. Alternatively, a downregulated pentose phosphate pathway may result in decreased NADPH generation and increased oxidative stress, which imbalances the redox system in F. graminearum , thereby retarding its growth and development [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be that excess MitoQ can stimulate the release of one-electron oxidizing species such as O 2 •− . There have been reports of excessive levels of oxidative stress induced by O 2 •− [ 34 ]. In addition, the O 2 •− anion radical is a key determinant of the overall effects of ROS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was found to reduce oxidative stress, resulting in cardiac protection by enhancing aerobic metabolism in vivo. Notably, the study revealed a significant increase in CA levels in the HPG group [5]. CA as a supplement in animal feed has a rich history dating back to 1937 when Pileggi et al discovered its positive effects on rat health, improving phosphorus utilization and preventing achondroplasia [6].…”
Section: Introductionmentioning
confidence: 90%